The Peaceful Mind Manual: A Protocol for Treating Anxiety in Persons With Dementia. (September 2013) - Paukert, Amber L.; Kraus-Schuman, Cynthia; Wilson, Nancy; Snow, A. Lynn; Calleo, Jessica; Kunik, Mark E.; Stanley, Melinda A.
Anxiety disorders are highly prevalent among individuals with dementia and have a significant negative impact on their lives. Peaceful Mind is a form of cognitive-behavioral therapy for anxiety in persons with dementia. The Peaceful Mind manual was developed, piloted, and modified over 2 years. In an open trial and a small randomized, controlled trial, it decreased anxiety and caregiver distress. The treatment meets the unique needs of individuals with dementia by emphasizing behavioral rather than cognitive interventions, slowing the pace, limiting the material to be learned, increasing repetition and practice, using cues to stimulate memory, including a friend or family member in treatment as a coach, and providing sessions in the home. The manual presented here includes modules that teach specific skills, including awareness, breathing, calming self-statements, increasing activity, and sleep management, as well as general suggestions for treatment delivery.